2019
DOI: 10.2139/ssrn.3326960
|View full text |Cite
|
Sign up to set email alerts
|

The Basel Capital Requirement, Lending Interest Rate, and Aggregate Economic Growth: An Empirical Study of Viet Nam

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
9
2
Order By: Relevance
“…The results of REM (Table 4) reflect that variable CAR has a negative impact on CGR with coefficient -0.00365 and variable CAR has positive effects on CGR with the significance level of 10%, indicating that CAR has an impact on CGR. This result contrasts with the expected sign and hypotheses; at the same time, this result disagrees with the analysis results of Ledgerwood (1999), Berrospide andEdge (2010), Catalán, Hoffmaister andHarun (2017), Phi, Hoang, Taghizadeh-Hesary and Yoshino (2019). Many PCFs maintain a high capital adequacy ratio of over 20% due to their limitations in loans providing ability and risk concerns in the recent period.…”
Section: Discussion Of the Model Of Factors Affecting Credit Growthcontrasting
confidence: 75%
See 1 more Smart Citation
“…The results of REM (Table 4) reflect that variable CAR has a negative impact on CGR with coefficient -0.00365 and variable CAR has positive effects on CGR with the significance level of 10%, indicating that CAR has an impact on CGR. This result contrasts with the expected sign and hypotheses; at the same time, this result disagrees with the analysis results of Ledgerwood (1999), Berrospide andEdge (2010), Catalán, Hoffmaister andHarun (2017), Phi, Hoang, Taghizadeh-Hesary and Yoshino (2019). Many PCFs maintain a high capital adequacy ratio of over 20% due to their limitations in loans providing ability and risk concerns in the recent period.…”
Section: Discussion Of the Model Of Factors Affecting Credit Growthcontrasting
confidence: 75%
“…When capital requirements of Basel II are between 1 -2%, the credit institutions lend more, which allows them to accumulate retained earnings through increased revenues. The quantitative impact of an increase in required capital is a sizable increase in lending (Phi, Hoang, Taghizadeh-Hesary, & Yoshino, 2019).…”
Section: Factors Affecting Credit Growth Of Pcfsmentioning
confidence: 99%
“…The results of REM in Table 4 showed that the variable CAR had a negative impact on CGR with coefficient -0.00343 with the significance level of 10%, indicating that CAR has an impact on CGR. This result contrasted with the expected sign and hypotheses, and disagreed with the analysis results of Ledgerwood (1999), Berrospide and Edge (2010), Phi et al (2019). Many PCFs maintained a high capital adequacy ratio of over 20% due to their limitations in loans providing ability and risk concerns in the recent period.…”
Section: Discussion Of the Model Of Factors Affecting Credit Growthcontrasting
confidence: 85%
“…When capital requirements of Basel II are between 1 -2%, the credit institutions lend more, which allows them to accumulate retained earnings through increased revenues. The quantitative impact of an increase in required capital is a sizable increase in lending (Phi et al, 2019).…”
Section: Factors Affecting Credit Growth Of Pcfmentioning
confidence: 99%
“…Additionally, the Basel Committee on Bank Supervision (BCBS) introduced Basel I in 1988 to provide guidance on the capital requirements for international banking institutions, then in 2006, Basel II was introduced to tighten guidance on supervision and market control. The financial crisis in 2007/8 ushered in the Basel III, which was introduced in 2010 not only to improve the amount of bank capital but also the quality of capital by incorporating leverage and liquidity standards (Phi et al., 2019). Under Basel II, the minimum capital requirement (MCR) was based on 1% VaR (Value at Risk) estimates with a holding period of at least 10 trading days.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%